2013
DOI: 10.1007/s10802-013-9762-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Error-Related Brain Activity in Six-Year-Old Children with Clinical Anxiety

Abstract: Anxiety disorders are the most frequently diagnosed form of psychopathology in children and often result in chronic impairment that persists into adulthood. Identifying neurobehavioral correlates of anxiety that appear relatively early in life would inform etiological models of development and allow intervention and prevention strategies to be implemented more effectively. The error-related negativity (ERN), a negative deflection in the event-related potential at fronto-central sites approximately 50 ms follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 74 publications
(94 reference statements)
18
70
0
Order By: Relevance
“…Individual variation in ERN magnitude is thought to index differences in sensitivity to error commission and defensive reactivity following mistakes (Hajcak, 2012; Weinberg, Riesel, & Hajcak, 2012). In keeping with the view that individuals with internalizing and externalizing tendencies have increased and decreased sensitivity to potential threat, respectively, studies have consistently found an increased ERN among internalizing individuals and a decreased ERN among externalizing individuals For example, work in adults and children suggests that the ERN magnitude is increased in individuals characterized by internalizing disorders or traits, such as obsessive-compulsive disorder (OCD; Carrasco et al, 2013; Endrass, Klawohn, Schuster, & Kathmann, 2008; Endrass et al, 2010; Gehring, Himle, & Nisenson, 2000; Hajcak, Franklin, Foa, & Simons, 2008; Riesel, Endrass, Kaufmann, & Kathmann, 2011; Ruchsow, Grön, et al, 2005), depression (Chiu & Deldin, 2007; Holmes & Pizzagalli, 2008, 2010; however, see: Olvet, Klein, & Hajcak, 2010; Weinberg, Klein, & Hajcak, 2012), generalized anxiety disorder (Weinberg, Olvet, & Hajcak, 2010; Xiao et al, 2011), heterogeneous anxiety disorders (Ladouceur, Dahl, Birmaher, Axelson, & Ryan, 2006; Meyer et al, 2013), OCD traits (Gründler, Cavanagh, Figueroa, Frank, & Allen, 2009; Hajcak & Simons, 2002; Santesso, Segalowitz, & Schmidt, 2006), trait anxiety (Meyer, Weinberg, Klein, & Hajcak, 2012; Pourtois et al, 2010), negative affect (Bush, Luu, & Posner, 2000; Hajcak, McDonald, & Simons, 2004), and behavioral inhibition (Amodio, Master, Yee, & Taylor, 2008; Boksem, Tops, Wester, Meijman, & Lorist, 2006; McDermott et al, 2009). In contrast, the ERN tends to be diminished in individuals characterized by externalizing disorders or traits, such as substance abuse (Franken, van Strien, Franzek, & van de Wetering, 2007; Luijten et al, 2014; Marhe, van de Wetering, & Franken, 2013), attention deficit hyperactivity disorder (ADHD; Albrecht et al, 2008; Groen et al, 2008; Hermann, Ziegler, Birbaumer, & Flor, 2002), psychopathy (Munro et al, 2007; Von Borries et al, 2010), trait impulsivity (Potts, George, Martin, & Barratt, 2006; Ruchsow, Spitzer, Grön, Grothe, & Kiefer, 2005), disinhibitory personality traits (Dikman & Allen, 2000), and externalizing traits (Hall, Bernat, & Patrick, 2007).…”
mentioning
confidence: 99%
“…Individual variation in ERN magnitude is thought to index differences in sensitivity to error commission and defensive reactivity following mistakes (Hajcak, 2012; Weinberg, Riesel, & Hajcak, 2012). In keeping with the view that individuals with internalizing and externalizing tendencies have increased and decreased sensitivity to potential threat, respectively, studies have consistently found an increased ERN among internalizing individuals and a decreased ERN among externalizing individuals For example, work in adults and children suggests that the ERN magnitude is increased in individuals characterized by internalizing disorders or traits, such as obsessive-compulsive disorder (OCD; Carrasco et al, 2013; Endrass, Klawohn, Schuster, & Kathmann, 2008; Endrass et al, 2010; Gehring, Himle, & Nisenson, 2000; Hajcak, Franklin, Foa, & Simons, 2008; Riesel, Endrass, Kaufmann, & Kathmann, 2011; Ruchsow, Grön, et al, 2005), depression (Chiu & Deldin, 2007; Holmes & Pizzagalli, 2008, 2010; however, see: Olvet, Klein, & Hajcak, 2010; Weinberg, Klein, & Hajcak, 2012), generalized anxiety disorder (Weinberg, Olvet, & Hajcak, 2010; Xiao et al, 2011), heterogeneous anxiety disorders (Ladouceur, Dahl, Birmaher, Axelson, & Ryan, 2006; Meyer et al, 2013), OCD traits (Gründler, Cavanagh, Figueroa, Frank, & Allen, 2009; Hajcak & Simons, 2002; Santesso, Segalowitz, & Schmidt, 2006), trait anxiety (Meyer, Weinberg, Klein, & Hajcak, 2012; Pourtois et al, 2010), negative affect (Bush, Luu, & Posner, 2000; Hajcak, McDonald, & Simons, 2004), and behavioral inhibition (Amodio, Master, Yee, & Taylor, 2008; Boksem, Tops, Wester, Meijman, & Lorist, 2006; McDermott et al, 2009). In contrast, the ERN tends to be diminished in individuals characterized by externalizing disorders or traits, such as substance abuse (Franken, van Strien, Franzek, & van de Wetering, 2007; Luijten et al, 2014; Marhe, van de Wetering, & Franken, 2013), attention deficit hyperactivity disorder (ADHD; Albrecht et al, 2008; Groen et al, 2008; Hermann, Ziegler, Birbaumer, & Flor, 2002), psychopathy (Munro et al, 2007; Von Borries et al, 2010), trait impulsivity (Potts, George, Martin, & Barratt, 2006; Ruchsow, Spitzer, Grön, Grothe, & Kiefer, 2005), disinhibitory personality traits (Dikman & Allen, 2000), and externalizing traits (Hall, Bernat, & Patrick, 2007).…”
mentioning
confidence: 99%
“…We have characterized this phenomenon as reflecting inefficient performance in anxiety because greater cognitive resources are allocated for no apparent behavioral gain (Eysenck et al 2007; Moser et al 2013; Moser et al 2014). Similar to adults, research in children has suggested that healthy subjects and their anxious peers do not differ in terms of behavioral performance (Meyer et al 2013). However, studies of young children have not fully characterized the nature of the anxiety-ERN relationship because they have yet to consider how anxiety may moderate the relationship between the ERN and behavioral performance.…”
mentioning
confidence: 99%
“…For example, ERN was elicited by a Go/no-Go task in children with anxiety disorder and controls. ERN in children with anxiety disorder was characterized by more negative wave, evident by the age of 6, independently of influence of maternal anxiety 9 .…”
Section: Ern Usefulnessmentioning
confidence: 90%